The impact of @jharnabhagwani content as instagram influencer - Moh Gifari Sono; Ardhi Goeliling; Irfandi Buamonabot; Tanti Widia Nurdiani; Dendi Pratama (Jurnal Komunikasi Profesional, 2023)
Businesses around Instagram influencers involve using these individuals to promote products or services to their followers. Businesses collaborates with influencers in a number of ways, including sponsored posts, affiliate marketing, and brand partnerships. This research examines Influencer marketing role and the impact on social engagement. the analysis technique will be using Instagram Analytics tool. The analytics tool functioned to simplify the old literature’s formula. With using Toolzu Analytics, we don’t need to calculate with complicated formula anymore but getting a complete multi-category data. The results of study show from cosplay being seen as sexualizing hobby, socially awkward, childish, and weird, become an art activity using make-up and show a real costume dress with good crafting and make-up. It’s also a proof that content can be visually pleasing without overdose of sexualization. It is also pretty unique that despite her strong domination of cosplay content, she managed to bring trend of business, education, and vegan from her top user’s interest.